2013
DOI: 10.1007/s10900-013-9765-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Sugary Drinks in the Food Retail Environment in Six NYC Neighborhoods

Abstract: Obesity is a national public health concern linked to numerous chronic health conditions among Americans of all age groups. Evidence suggests that discretionary calories from sugary drink consumption have been a significant contributor to excess caloric intake among both children and adults. Research has established strong links between retail food environments and purchasing habits of consumers, but little information exists on the sugary drink retail environment in urban neighborhoods. The objective of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Shelf-space and orientation within supermarkets and convenience stores in our neighborhood would likely be set up in such a way as to direct us to energy-dense, low nutrient foods [318,319,320,321,322]. Also inside, in-store marketing may direct us to a significant variety of (relatively) low-priced, high-sugar beverages [323]. On the other hand, healthier staples such as low-fat dairy products may be less available and more expensive [324].…”
Section: Behavioral Reinforcementmentioning
confidence: 99%
“…Shelf-space and orientation within supermarkets and convenience stores in our neighborhood would likely be set up in such a way as to direct us to energy-dense, low nutrient foods [318,319,320,321,322]. Also inside, in-store marketing may direct us to a significant variety of (relatively) low-priced, high-sugar beverages [323]. On the other hand, healthier staples such as low-fat dairy products may be less available and more expensive [324].…”
Section: Behavioral Reinforcementmentioning
confidence: 99%
“…This research identified drinks as prominent characteristics the limited availability of healthy foods and beverages, coupled with cost and quality concerns, the ubiquity of unhealthy foods and other unhealthy foods, and high consumption of sugary beverages. [51][52][53][54][55][56][57][58][59][60] Within the IOTF framework, identifying potential points of intervention (issue 2) and instruments with which to respond (issue 3) are underpinned by the choice to view obesity as an issue amenable to successful local government intervention. Kingdon conceptualizes this as the differentiation between condition and problem, subject to a "perceptual interpretative element".…”
Section: Evidence-driven Framing Of the Problem And Possible Intervenmentioning
confidence: 99%
“…Research conducted among adolescents found that frequent exposure to alcohol promotions in stores was associated with a 50% increase in the likelihood of ever drinking [ 27 ]. Additionally, a study conducted in New York City found that stores were more likely to display sugary drinks promotions in neighborhoods with higher intakes of sugar-sweetened beverages compared to stores in neighborhoods with lower intakes of sugar-sweetened beverages [ 28 ]. Lastly, among low-income public housing residents, higher counts of alcohol print promotions and lower counts of low-calorie food print promotions in stores and restaurants were associated with higher dietary fat intake [ 29 ].…”
Section: Introductionmentioning
confidence: 99%